EVALUASI PROGRAM PENGEMBANGAN KECAMATAN (PPK) DI KELURAHAN KABUPATEN, KECAMATAN KLATEN TENGAH, KABUPATEN KLATEN - Suprapto, Joko - (JI@P, 2014)
Joko Suprapto, 2012. Evaluasi Program Pengembangan Kecamatan (PPK) diKelurahan Kabupaten, Kecamatan Klaten Tengah, Kabupaten Klaten. Thesis(unpublished). Universitas Slamet Riyadi.It is considered that the poverty reduction programs launched by thegovernment in the past tended not in the frame of community empowerment,but on the other hand the programs created the dpendency of the poor upon thestate and outside aids. In overcoming that problem, the government launcheswhat so called Sub District Development Program (Program PengembanganKecamatan/ PPK). It is expected that such program enable to createemployment for the poor which in turn, is able to increase the poorâs income.This research was conducted to evaluate the degree of success as well offailure, and the degree of effectiveness and efficiency of the program. Theresearch site is in Klaten Sub District, Klaten Regency. Strategy of the researchused qualitative reserch method. Purposive sampling was chosen to select theinformen. Informen in this study were Activity Management Team (TimPengelola Kegiatan), LPM, facilitators, Monitoring Team, Maintenance Team,and vocational training beneficiaries. Interview and Focus Group Discussionwere employed for collecting data. Interactive data analysis model asrecommended by Miles and Buberman was done to analyse data. To validatethe finding, triangulation technique by comparing the other data as well as theother sources was used. Research result shows that the plan, implementationand evaluation of the program are supported by either program implementer atlocal level, human resources as well as financial resource, or by the existingfacilities. Research result indicates that human resources qualitatively as well asquantitatively have been fulfilled, community awareness and communityparticipation found high. Implementation of the program found to focus forincreasing community well being, community skill, reducing unemployementlevel, and empowering community.Keyword: Evaluation, Sub District Development Program (PPK), plan, implementation,community empowerment.